Tage Frid woodworking profile. - Frid, Tage.; Taunton Press ([Newtown, CT] : Taunton Press, 2005)
Woodworker Tage Frid builds several pieces and discusses how his philosophy of design around construction plays into his work. Frid also demonstrates such woodworking basics as sharpening a chisel and cabinet scraper as well as how to make multiple spine joints and cut half-blind dovetails.
Tage Frid.
Keywords: Instructional films; Woodwork